A comparative study of the modified high voltage olivine-phosphate LiMPO4 (M = Fe, Mn, Co, Ni) as promising cathode materials for next-generation rechargeable batteries - Manfo, Theodore Azemtsop; Laaksonen, Hannu (Elsevier, 2026)
The growing demand for energy storage has driven extensive research into advanced cathode materials for lithium-ion batteries (LIBs), where cathode chemistry critically governs safety, cost, and electrochemical performance. Olivine lithium metal phosphates (LiMPO4) are promising cathode candidates due to their structural robustness and thermal stability. Rietveld refinement confirms an orthorhombic olivine structure (Pnma), with lithium occupying octahedral sites and Mn2+ and Co2+ substituting for Fe2+. Cell parameters and unit-cell volume increase with Mn substitution; while LiFePO4 (LFP) exhibits favorable electrochemical stability, LiMnPO4 (LMP) offers higher operating potential but suffers from sluggish lithium intercalation kinetics. Recent studies demonstrate that partial substitution with Co and Ni can significantly enhance electrochemical performance by modifying lithium diffusion pathways and energetics within the olivine framework. This paper summarizes recent progress on olivine cathodes, including LiCoPO4 (LCP) and LiNiPO4 (LNPO), which exhibit operating potentials exceeding 5.0 V versus Li+/Li. Strategies to overcome intrinsic limitations, such as particle size reduction, surface modification, and cation doping, are critically discussed, highlighting clear correlations between structure and electrochemical behavior. Key material descriptors, including cohesive energy, lithium intercalation energetics, and electrochemical stability, are examined. Finally, emerging opportunities and remaining challenges for olivine phosphates in solid-state and aqueous energy storage systems are outlined, providing a forward-looking perspective for next-generation LIB development.
Keywords: LiMPO4; Olivine cathodes; Lithium-ion batteries; High-voltage energy storage; Surface engineering; Solid-state batteries; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Sähkötekniikka|en=Electrical Engineering|